Perspectives of analysis of Gas industry in Portugal. The case of Lisbon in 19th century - Matos, Ana Cardoso de (2018)
The emerge of gas lighting in Portugal occurred some years later in relation to the other European countries, The situation of political disturbance, which existed in the country during the initial decades of the 19th century , did not raise favorable conditions to implement big investments to modernize the cities. Only in 1834 the Lisbon City Council started promoting city’s gas lighting system. However, in spite of emerging from this date on various proposals from nationals and foreigners, it took further twelve years to realize the first contract with a private company – Companhia Lisbonense de Iluminação a Gás. This text analyze the establishment of a gas network in Lisbon.